การบริหารโรงเรียนดนตรี ตามแนวคิดการบริหารแบบมุ่งคุณภาพทั้งองค์การ MUSIC SCHOOL ADMINISTRATION BASED ON TOTAL QUALITY MANAGEMENT - ธนาวัฒนเจริญ ปรีชญา; อุสาโห ชญาพิมพ์ (An Online Journal of Education, 2018)
Abstract This research aimed to 1) study of music school management 2) study the issues cause from current music school management 3) study development approach of music school management according to music school administration based on total quality management. Population was schools under the Non-Formal Education Promotion Unit, Office of The Private Education Commission (OPEC) in Bangkok in 2014 totaling 140 schools. The sample consisted of 230 people selected purposively from 46 schools and the information was received from executives, teachers, administrative staffs, students and parents. This research used questionnaire and a proper assessment possibility form to analyze data by using mean and standard deviation (SD) The results found that according to music school administration based on total quality management area of customer focus, continues improvement and total participation were at high level of satisfaction and the issues from operation were at low level including academic affair administration, human resource management and general administration but in the area of societal networking was rated at medium level and the issues from operation was at low level. The music school administration should be improve are total 15 approaches including 8 approaches in social network, 2 approaches in continuous improvement and 5 approaches in customer focus. There is no approach need to improve in members’ participation.